Znaczenie formuły ΚΛΕΟΣ ΑΦΘΙΤΟΝ w kontekście nieśmiertelności Achillesa - Chruściak, Ilona (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2014)
Two accounts of Achilles’ immortality – that found in a symbolic dimension, based on his glory and the memory of posterity, and that found in a cultic and eschatological dimension – co-exist in the Iliad on two different levels in creating the integrity of the whole. The myth exists only in allusions and the recollections of the poet.
Keywords: Homer; Iliad; Achilles; epic poetry; oral formulaic theory